Figs 45–47. Pseudowigwamma scenozonion TEM whole mounts. 45 in Coccolithophorids in Polar Waters: Wigwamma spp. Revisited ... - Thomsen, Helge A.; Østergaard and Mikal Heldal, Jette B. (Zenodo, 2013)
Figs 45–47. Pseudowigwamma scenozonion TEM whole mounts. 45 – complete cell (Arctic / NEW); 46 – detail showing base plate calcification (single layer) and the odd enlarged rim crystallite; Notice also the radial patterning of the organic base plate surface (Arctic Station); 47 – complete cell (Arctic Station). ... : Published as part of Thomsen, Helge A. & Østergaard and Mikal Heldal, Jette B., 2013, Coccolithophorids in Polar Waters: Wigwamma spp. Revisited, pp. 237-256 in Acta Protozoologica 52 on page 252, DOI: 10.4467/16890027AP.14.007.1444, http://zenodo.org/record/13193273 ...